Film-forming material and method for producing coating film
By adjusting the microcrystalline size ratio of rare earth fluoride and rare earth fluoride oxide, and using spraying or PVD method, the problem of uneven melting of film-forming materials in the prior art is solved, and plasma etching is achieved Preparation of high corrosion resistance and dense film materials.
Patent Information
- Application Number
- CN202380042639.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-09
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-03
AI Technical Summary
The melting degree of existing rare earth fluoride and rare earth fluoride oxide film forming materials is uneven, resulting in insufficient corrosion resistance of the obtained film to plasma etching.
By adjusting the crystallite size ratio of rare earth fluoride and rare earth fluoride oxide, ensuring that it is above 0.90 and below 1.35, and combining with the film formation process of spraying or PVD, film materials with excellent corrosion resistance are prepared. .
The corrosion resistance of the film to plasma etching is improved, the density and corrosion resistance of the film are ensured, and it is suitable for semiconductor manufacturing devices.
Smart Images

Figure CN119256111A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a film-forming material containing a rare earth fluoride and a rare earth oxyfluoride and a method for producing a film. Background Art
[0002] Rare earth oxides such as Y2O3, rare earth fluorides such as YF3, and rare earth oxyfluorides such as Y5O4F7 are highly corrosion-resistant ceramics, and their films and sintered bodies are used as protective materials in semiconductor manufacturing processes.
[0003] In particular, it is known that a film or sintered body of a film-forming material containing a rare earth oxyfluoride has high chemical plasma corrosion resistance and can shorten the aging time of semiconductor manufacturing equipment.
[0004] As a film-forming material containing a rare earth oxyfluoride and a rare earth fluoride, the film-forming materials of Patent Documents 1 to 3 are known.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: U.S. Patent Application Publication No. 2015 / 096462
[0008] Patent Document 2: U.S. Patent Application Publication No. 2016 / 326623
[0009] Patent Document 3: U.S. Patent Application Publication No. 2017 / 114440 Summary of the invention
[0010] The degree of melting of the film-forming materials described in the prior art documents varies greatly, and depending on the film-forming conditions, melting may be partially insufficient. Therefore, the corrosion resistance of the obtained film to plasma etching may be insufficient.
[0011] Therefore, an object of the present invention is to provide a film-forming material containing a rare earth fluoride and a rare earth oxyfluoride, which can eliminate the various disadvantages of the above-mentioned prior art.
[0012] The inventors of the present invention have conducted extensive research on the composition of film-forming materials containing rare earth fluorides and rare earth fluoride oxides to effectively improve the corrosion resistance to plasma etching. As a result, they found that the crystallite size of rare earth fluorides is preferably the same as or slightly larger than the crystallite size of rare earth fluoride oxides.
[0013] The present invention has been completed based on the above findings, and provides the following [1] to
[11] .
[0014] [1] A film-forming material, wherein a rare earth fluoride (REF3) and a rare earth fluoride oxide (RE-OF) are observed in X-ray diffraction measurement, and the crystallite size (S REF3 ) relative to the crystallite size of RE-OF (S RE-O-F ) ratio (S REF3 / S RE-O-F ) is greater than or equal to 0.90 and less than or equal to 1.35.
[0015] [2] The film-forming material according to [1], wherein each of REF3 and RE-OF has a crystallite size of 40 nm or more and 100 nm or less.
[0016] [3] The film-forming material according to [1] or [2], wherein the average particle size of the primary particles observed under a scanning electron microscope (SEM) is 0.1 μm or more and 1.0 μm or less.
[0017] [4] The film-forming material according to any one of [1] to [3], which is in the form of particles.
[0018] [5] The film-forming material according to [4], wherein the porosity in the internal cross section of the particle observed by SEM is 10% or more and 35% or less.
[0019] [6] The film-forming material according to [4] or [5], wherein the crushing pressure measured by a SEM indenter is 25 kPa or more and 130 kPa or less.
[0020] [7] The film-forming material according to [4], wherein the average particle size of the particles is 10 μm or more and 60 μm or less.
[0021] [8] The film-forming material according to any one of [1] to [7], which has a bulk density of 1.3 g / cm 3 The above particles.
[0022] [9] The film-forming material according to any one of [1] to [8], wherein the oxygen content is 1 mass % or more and 9 mass % or less.
[0023]
[10] The film-forming material according to any one of [1] to [9], wherein the rare earth element (RE) is at least one selected from yttrium (Y), gadolinium (Gd), erbium (Er) and ytterbium (Yb).
[0024]
[11] A method for producing a film, comprising forming a film of the film-forming material described in any one of [1] to
[10] by a sputtering method or a PVD method. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is an XRD pattern used for measuring the crystallite size in Example 1.
[0026] Figure 2 This is a scanning electron microscope photograph used for the porosity measurement of Example 1.
[0027] Figure 3 This is a scanning electron microscope photograph of Example 1 before the measurement of the crushing pressure is started.
[0028] Figure 4 This is a scanning electron microscope photograph at the end of the measurement of the crushing pressure of Example 1. DETAILED DESCRIPTION
[0029] Hereinafter, the present invention will be described based on preferred embodiments thereof.
[0030] 1. Film-forming materials
[0031] The film-forming material of the present invention contains a rare earth element (hereinafter also referred to as RE), and rare earth fluoride (hereinafter also referred to as REF3) and rare earth oxyfluoride (hereinafter also referred to as RE-OF) are observed in X-ray diffraction measurement.
[0032] As rare earth elements (RE), 16 elements including scandium (Sc), yttrium (Y), lanthanum (La), cerium (Ce), praseodymium (Pr), neodymium (Nd), samarium (Sm), europium (Eu), gadolinium (Gd), terbium (Tb), dysprosium (Dy), holmium (Ho), erbium (Er), thulium (Tm), ytterbium (Yb) and lutetium (Lu) can be listed. The film-forming material of the present invention contains at least one of these 16 rare earth elements. From the viewpoint of further improving the corrosion resistance of the film formed by the film-forming material of the present invention using the method described later, among these elements, RE is preferably at least one selected from yttrium (Y), gadolinium (Gd), erbium (Er) and ytterbium (Yb), and yttrium (Y) is particularly preferred.
[0033] Rare earth oxyfluoride (RE-OF) is a compound containing a rare earth element (RE), oxygen (O), and fluorine (F). RE-OF may be a compound (RE1O1F1) in which the molar ratio of the rare earth element (RE), oxygen (O), and fluorine (F) is RE:O:F=1:1:1, or may be other forms of rare earth oxyfluoride (RE5O4F7, RE7O6F9, RE4O3F6, etc.). From the viewpoint of further improving the ease of manufacturing the oxyfluoride and the corrosion resistance of the film formed by the method described later, RE-OF is preferably composed of REO x F y(0.5≤x≤1, 1≤y≤2). In particular, from the above viewpoint, in the above formula, 0.6≤x≤0.9 is more preferred, and 0.7≤x≤0.82 is further preferred. In addition, 1.2≤y≤1.8 is more preferred, and 1.35≤y≤1.6 is further preferred. In addition, in the above formula, 2x+y=3 is preferably satisfied.
[0034] From the above viewpoints, the rare earth oxyfluoride is preferably at least one selected from RE3O2F5, RE4O3F6, RE5O4F7, RE6O5F8 and RE7O6F9, and is particularly preferably RE5O4F7.
[0035] In the film-forming material of the present invention, the rare earth elements in the rare earth oxyfluoride and the rare earth fluoride may be the same or different, but are preferably the same. Furthermore, the rare earth oxyfluoride is preferably an oxyfluoride of a single rare earth element, and is particularly preferably a single phase. The single phase means that in XRD analysis, a phase of a single compound of the rare earth oxyfluoride is observed, and no other crystalline phase of the rare earth oxyfluoride is observed.
[0036] To obtain a RE-OF film-forming material having a desired composition, for example, the amount of hydrofluoric acid added may be adjusted in the first step of a suitable method for producing the film-forming material described below, or the calcination atmosphere and calcination temperature may be appropriately controlled in the fourth step.
[0037] When the film-forming material of the present invention contains REF3 and RE-OF as described above, the content of REF3 in the film-forming material can be controlled by, for example, adjusting the amount of hydrofluoric acid added dropwise in the first step of a suitable method for producing the film-forming material described below.
[0038] It should be noted that it is not easy to accurately measure the amount of fluorine contained in the film-forming material of the present invention. For this reason, in the present invention, when the film-forming material is subjected to X-ray diffraction measurement using Cu-Kα rays, the content of REF3 is estimated from the value of the relative intensity of the diffraction peak of the maximum height of RE-OF (hereinafter also referred to as the main peak) of the main peak of REF3 in the scanning range of 2θ=20°~60°. Specifically, in the X-ray diffraction measurement of particles using Cu-Kα rays, the ratio (S1 / S2) of the intensity of the main peak of RE-OF observed in the range of 2θ=20°~60° and the intensity of the main peak of REF3 observed in the same range (S2) is calculated. For example, if S1 / S2 is greater than 0.05 and less than 35, the corrosion resistance of the film obtained from the film-forming material is particularly excellent, so it is preferred. From this viewpoint, S1 / S2 is more preferably 0.1 or more and 15 or less, further preferably 0.5 or more and 10 or less, and particularly preferably 1 or more and 7 or less.
[0039] In the XRD analysis using Cu-Kα radiation in the range of 2θ=20° to 60°, the main peak of Y5O4F7 is the (151) peak, which is usually observed at 2θ=28.11°. In addition, the main peak of Y6O5F8 is the (161) peak, which is usually observed at 2θ=28.14°. In addition, the main peak of Y7O6F9 is the (171) peak, which is usually observed at 2θ=28.14°.
[0040] The main peak of Gd4O3F6 is the (021) peak, which is usually observed at 2θ=27.60°.
[0041] The main peak of Er5O4F7 is the (151) peak, which is usually observed at 2θ=28.25°.
[0042] The main peak of Yb5O4F7 is the (151) peak, which is usually observed at 2θ=28.50°.
[0043] The main peak of Sm4O3F6 is the (111) peak, which is usually observed at 2θ=27.59°.
[0044] The main peak of Eu4O3F6 is the (111) peak, which is usually observed at 2θ=28.04°.
[0045] The main peak of Lu7O6F9 is the (171) peak, which is usually observed at 2θ=28.60°.
[0046] The main peak of Y1O1F1 is the (012) peak, which is usually observed at 2θ=28.74°.
[0047] The main peak of Gd1O1F1 is the (012) peak, which is usually observed at 2θ=28.20°.
[0048] In addition, the main peak of YF3 is the (111) peak, which is usually observed at 2θ=27.88°.
[0049] The main peak of GdF3 is the (111) peak, which is usually observed at 2θ=27.54°.
[0050] The main peak of ErF3 is the (111) peak, which is usually observed at 2θ=27.95°.
[0051] The main peak of YbF3 is the (111) peak, which is usually observed at 2θ=27.98°.
[0052] The main peak of SmF3 is the (111) peak, which is usually observed at 2θ=27.33°.
[0053] The main peak of EuF3 is the (111) peak, which is usually observed at 2θ=27.46°.
[0054] The main peak of LuF3 is the (111) peak, which is usually observed at 2θ=27.97°.
[0055] Among them, when RE-OF and REF3 are observed, when the main peaks are detected at close positions (within 0.4°) due to the combination of compositions, such as Y5O4F7 and YF3, Gd4O3F6 and GdF3, and Er5O4F7 and ErF3, the measurement can be performed as follows.
[0056] Specifically, the intensity of the peak corresponding to the predetermined surface described later (I S ) divided by the relative intensity of the specified surface (the intensity of the main peak is 100) (the intensity recorded in the PDF card (Powder Diffraction Filecard): I T ) were used as the intensity of the main peak (I M ).
[0057] ※I M =I S / I T ×100
[0058] The peak of the (010 0) plane of Y5O4F7 is generally observed at 2θ=32.29°, and the relative intensity with respect to the main peak is 23.4%.
[0059] The peak of the (100) plane of Gd4O3F6 is generally observed at 2θ=31.77°, and the relative intensity with respect to the main peak is 14.5%.
[0060] The peak of the (171) plane of Er5O4F7 is generally observed at 2θ=32.48°, and its relative intensity to the main peak is 14.2%.
[0061] The peak of the (002) plane of Sm4O3F6 is generally observed at 2θ=31.91°, and the relative intensity with respect to the main peak is 80%.
[0062] The peak of the (002) plane of Eu4O3F6 is generally observed at 2θ=32.41°, and the relative intensity with respect to the main peak is 80%.
[0063] The peak of the (014 0) plane of Lu7O6F9 is generally observed at 2θ=32.87°, and the relative intensity with respect to the main peak is 19%.
[0064] The predetermined peak of REF3 can be a peak of the (020) plane.
[0065] For example, the peak of the (020) plane of YF3 is generally observed at 2θ=25.98°, and the relative intensity with respect to the main peak is 67.6%.
[0066] The peak of the (020) plane of GdF3 is generally observed at 2θ=25.47°, and the relative intensity with respect to the main peak is 60.0%.
[0067] The peak of the (020) plane of ErF 3 is generally observed at 2θ=26.03°, and the relative intensity with respect to the main peak is 75.0%.
[0068] The peak of the (020) plane of SmF3 is generally observed at 2θ=25.22°, and the relative intensity with respect to the main peak is 85%.
[0069] The peak of the (020) plane of EuF3 is generally observed at 2θ=25.37°, and the relative intensity with respect to the main peak is 70%.
[0070] The peak of the (020) plane of LuF3 is generally observed at 2θ=26.33°, and the relative intensity with respect to the main peak is 90%.
[0071] The error of the peak position is preferably within ±0.05°, more preferably within ±0.03°, further preferably within ±0.02°, and most preferably within ±0.01°.
[0072] It should be noted that, when the film-forming material of the present invention comprises Yb5O4F7 and YbF3, when it comprises Y1O1F1 and YF3, and when it comprises Gd1O1F1 and GdF3, the difference in the positions of the main peaks thereof is 0.52°, 0.86° and 0.66°, respectively, in terms of 2θ, which are all greater than 0.4°. Therefore, it is preferred to use the intensity of the main peak itself to calculate S1 / S2.
[0073] For each record of the main peak ratio of RE-OF and REF3 recorded in this specification, it can be either a case where the main peak height ratio is calculated using the peak height (intensity) of the main peak itself and the main peak height ratio is calculated and the case is consistent, or as described above, the main peak height ratio is calculated by dividing the peak height (intensity) of the non-main peak by the main peak converted height obtained by setting the height (intensity) of the main peak recorded on the PDF card to 100. Assuming that the measurement can be performed by these two methods, if one case is consistent with the ratio recorded in this specification, it is deemed to be consistent even if it is not consistent with the other case.
[0074] Since the film-forming material of the present invention contains RE-OF, it contains oxygen. The amount of oxygen contained in the film-forming material (hereinafter also referred to as oxygen content) is preferably greater than 1% by mass and less than 9% by mass. By setting the oxygen content of the film-forming material to be greater than 1% by mass, when the film-forming material of the present invention is formed by a spraying method, for example as described later, the film-forming material can be stably supplied during spraying, thereby easily obtaining a smooth sprayed film. On the other hand, by setting the oxygen content to be less than 9% by mass, the generation of a substance that is a cause of reducing the corrosion resistance of the film-forming material, namely, rare earth oxides described later, can be effectively prevented in the film-forming material, thereby effectively preventing the reduction in the corrosion resistance of the formed film. From these viewpoints, the oxygen content of the film-forming material is more preferably greater than 1% by mass and less than 7% by mass, and further preferably greater than 2% by mass and less than 5% by mass. To adjust the amount of oxygen contained in the film-forming material to fall within the above range, for example, the amount of hydrofluoric acid added dropwise in the first step or the firing conditions in the fourth step may be adjusted in a suitable method for producing the film-forming material described later.
[0075] The oxygen content of the film-forming material can be measured by a melting-infrared absorption method in an inert gas (using a halogen trap).
[0076] From the viewpoint of corrosion resistance of the film, in particular, corrosion resistance to chlorine-based gases, the film-forming material of the present invention preferably contains no rare earth element oxides, i.e., RE, as much as possible. z O W (hereinafter also referred to as rare earth oxides). In order to minimize the RE contained in the film-forming powder of the present invention z O W For example, a moderately highly reactive rare earth raw material may be used in the first step of a suitable method for producing the film-forming material described later, and the ratio (F / RE) of the number of moles of the rare earth element (RE) from the rare earth compound to the number of moles of fluorine atoms (F) from hydrofluoric acid may be controlled to be within a suitable range described later, or the sintering conditions may be adjusted in the fourth step of the method.
[0077] Since the RE contained in the film-forming powder of the present invention is quantitatively determined by chemical analysis, z O W It is not easy to determine the amount of RE, so in the present invention, the intensity of the diffraction peak when the film-forming powder is subjected to X-ray diffraction measurement is used to estimate the RE. z O wSpecifically, for the film-forming powder of the present invention, in the X-ray diffraction measurement using Cu-Kα rays, the ratio (S0 / S1) of the intensity of the main peak of the rare earth oxide observed in the range of 2θ=20° to 60° and the intensity of the main peak of the rare earth fluoride oxide observed in the same range is determined. The X-ray diffraction measurement used in the present invention is performed using a powder X-ray diffraction measurement method.
[0078] In the present invention, S0 / S1 is preferably 0.1 or less, more preferably 0.05 or less, further preferably 0.01 or less, and particularly preferably 0.005 or less. The smaller S0 / S1 is, the better, and most preferably 0. In the present invention, by making S0 / S1 0.1 or less, particularly 0.05 or less, not only the corrosion resistance to fluorine-based plasma but also the corrosion resistance to chlorine-based plasma is high.
[0079] For rare earth oxyfluorides (RE-OF), rare earth oxides (RE z O W The maximum diffraction peak of ) and rare earth fluoride (REF3) obtained by powder X-ray diffraction measurement using Cu-Kα rays is usually observed in the range of 2θ=20° to 60°.
[0080] For example, the main peak of Y2O3 is (222), which is usually observed at 2θ=29.14°.
[0081] The main peak of Gd2O3 is (222), which is usually observed at 2θ=28.57°.
[0082] The main peak of Er2O3 is (222), which is usually observed at 2θ=29.21°.
[0083] The main peak of Yb2O3 is (222), which is usually observed at 2θ=29.63°.
[0084] The main peak of Sm2O3 is (222), which is usually observed at 2θ=28.26°.
[0085] The main peak of Eu2O3 is (222), which is usually observed at 2θ=28.42°.
[0086] The main peak of Lu2O3 is (222), which is usually observed at 2θ=29.75°.
[0087] It should be noted that rare earth oxides (RE z O W) is not close to the peak of rare earth fluoride oxide (RE-OF) and rare earth fluoride (REF3), so RE can be used directly in the determination of S0 / S1. z O W The intensity of the main peak.
[0088] It should be noted that when the film-forming material of the present invention is produced by firing oxalate or carbonate in the atmosphere, the rare earth oxide (RE z O W ) is usually a sesquioxide (RE2O3) with z=2 and w=3. Cerium oxide is usually CeO2 with z=1 and w=2, and praseodymium oxide is usually Pr6O with z=6 and w=11. 11 Terbium oxide is usually Tb4O7 with z = 4 and w = 7. Other forms of oxides, such as Ce2O3, Pr2O3, PrO2, EuO, etc., can be manufactured under special manufacturing conditions, but they will return to the above-mentioned normal form when placed in the atmosphere, so the above-mentioned normal form is preferred.
[0089] The film-forming material of the present invention preferably has a crystal phase other than oxyfluorides of rare earth elements substantially consisting of only fluorides of rare earth elements represented by REF3 in XRD analysis. "The crystal phase other than oxyfluorides of rare earth elements substantially consisting of only fluorides of rare earth elements represented by REF3" preferably means that in XRD analysis using Cu-Kα rays and setting 2θ=20 to 60° as the scanning range, the peak height of the main peak of the crystal phase derived from oxyfluorides of rare earth elements and compounds other than fluorides of rare earth elements represented by REF3 (hereinafter sometimes also described as "other components") is 10% or less relative to the peak height of the main peak of the crystal phase derived from RE-OF, more preferably means 5% or less, further preferably means 3% or less, and most preferably means 1% or less.
[0090] The film-forming material of the present invention is a film-forming material in which the crystallite size of REF3 satisfies a predetermined relationship with the crystallite size of RE-OF. Specifically, the crystallite size of RE-OF obtained from the half-peak width of a specific peak of RE-OF in X-ray diffraction measurement is referred to as S. RE-O-F , the crystallite size of REF3 obtained from the half-peak width of the specific peak of REF3 is defined as S REF3 When the ratio of the two (S REF3 / S RE-O-F ) is 0.90 or more and 1.35 or less. REF3 / S RE-O-FIn this range, the corrosion resistance of the film formed by the film-forming material to plasma etching is improved. REF3 / S RE-O-F Preferably, it is 1.00 or more and 1.35 or less, more preferably 1.02 or more and 1.30 or less, and further preferably 1.04 or more and 1.25 or less. The crystallite size is obtained by using the sheller formula, for example, it can be obtained by the method described in the embodiments described later, but other machine models can also be used as long as the measurement accuracy is equal or higher. Since the main peak of RE-OF is close to the main peak of REF3, it is difficult to obtain the half-peak width of at least one of them. Therefore, the half-peak width of a specific peak different from the main peak and not close to other peaks is obtained to calculate the crystallite size.
[0091] In addition, the 2θ angle of the specific peak shown below represents the angle in the XRD analysis using Cu—Kα rays in the range of 2θ=20° to 60°.
[0092] The specific peak used to determine the crystallite size of RE-OF will be described.
[0093] The specific peak of Y5O4F7 is the (0 10 0) peak, which is usually observed at 2θ=32.29°.
[0094] The specific peak of Gd4O3F6 is the (100) peak, which is usually observed at 2θ=31.77°.
[0095] The specific peak of Er5O4F7 is the (171) peak, which is usually observed at 2θ=32.48°.
[0096] The specific peak of Yb5O4F7 is the (171) peak, which is usually observed at 2θ=32.82°.
[0097] The specific peak of Sm4O3F6 is the (002) peak, which is usually observed at 2θ=31.91°.
[0098] The specific peak of Eu4O3F6 is the (002) peak, which is usually observed at 2θ=32.41°.
[0099] The specific peak of Lu7O6F9 is the (0 14 0) peak, which is usually observed at 2θ=32.87°.
[0100] The specific peak of Y1O1F1 is the (012) peak, which is usually observed at 2θ=28.74°.
[0101] The specific peak of Gd1O1F1 is the (012) peak, which is usually observed at 2θ=28.20°.
[0102] Next, the specific peak used to determine the crystallite size of REF3 will be described.
[0103] When determining the crystallite size of REF3, the (020) peak is used.
[0104] For example, a specific peak of YF3 is a (020) peak, which is usually observed at 2θ=25.98°.
[0105] The specific peak of GdF3 is the (020) peak, which is usually observed at 2θ=25.47°.
[0106] The specific peak of ErF3 is the (020) peak, which is usually observed at 2θ=26.03°.
[0107] The specific peak of YbF3 is the (020) peak, which is usually observed at 2θ=26.24°.
[0108] The specific peak of SmF3 is the (020) peak, which is usually observed at 2θ=25.22°.
[0109] The specific peak of EuF3 is the (020) peak, which is usually observed at 2θ=25.37°.
[0110] The specific peak of LuF3 is the (020) peak, which is usually observed at 2θ=26.33°.
[0111] It should be noted that, in the case where the film-forming material of the present invention contains Yb5O4F7 and YbF3, the case where it contains Y1O1F1 and YF3, and the case where it contains Gd1O1F1 and GdF3, when calculating the peak intensity ratio of the two, it is preferred to use their respective main peaks as described above, and when calculating the crystallite size of the two, it is preferred to use the above-mentioned specific peaks because it is preferred to separate the peaks more reliably.
[0112] The crystallite size can be calculated using the above-mentioned specific peak according to "12. Measurement of crystallite size and inhomogeneous strain" of JIS K 0131-1996 "General Rules for X-ray Diffraction Analysis" using the formula (8) described in the JIS, namely the so-called Sheller formula.
[0113] At this time, the diffraction data based on CuKα rays are separated into the diffraction data based on Cu-Kα1 rays and Cu-Kα2 rays, and the diffraction pattern of only Cu-Kα1 rays is drawn to obtain the half-peak width and diffraction angle of the above-mentioned specific peak. In addition, the standard substance is measured and the half-peak width is corrected.
[0114] Note that the calculation of the crystallite size by the above method can be performed using various X-ray analysis software, for example, PDXL2 (manufactured by Rigaku Corporation).
[0115] In S REF3 / S RE-O-F The reason why the corrosion resistance to plasma etching is improved when it is within the above range is not clear, but the inventors have conducted the following research. Generally, rare earth fluoride oxides have a higher melting point than rare earth fluorides. If the crystallite size of rare earth fluorides having a lower melting point than rare earth fluoride oxides is the same to slightly larger than that of rare earth fluoride oxides, the particles of each composition melt at the same time and melt evenly, thereby easily obtaining a smooth film. In addition, the particle energy when the substrate collides is the same for rare earth fluoride oxides and rare earth fluorides, and it is easy to obtain a uniform film structure. Based on the above reasons, the corrosion resistance of the film to plasma etching is improved.
[0116] Crystallite size S of REF3 REF3 It is preferably 40 nm to 100 nm, more preferably 50 nm to 95 nm, and even more preferably 60 nm to 90 nm. REF3 When the S is 40 nm or more, it has the advantage of being able to suppress structural defects of the crystal grains and easily obtain relatively uniform particles with good crystallinity. REF3 When the particle size is 100 nm or less, there is an advantage that excessive grain growth can be suppressed and the meltability of each particle is easily improved.
[0117] In addition, the crystallite size S of RE-OF RE-O-F It is preferably 40 nm to 100 nm, more preferably 50 nm to 95 nm, and even more preferably 60 nm to 90 nm. RE-O-F When the thickness is 40 nm or more and 100 nm or less, it has the same properties as the above-mentioned S REF3 Same advantages.
[0118] In order to get S REF3 and S RE-O-F The film-forming material that meets the above conditions can, for example, appropriately select the rare earth compound in the first step of the preferred manufacturing method of the film-forming material of the present invention described later, and further appropriately adjust the crushing conditions in the third step and the sintering temperature in the fourth step.
[0119] The BET specific surface area of the film-forming material of the present invention is preferably 0.1 m 2 / g or more and 10m 2 / g or less, more preferably 0.5m 2 / g or more and 8m 2 / g or less, more preferably 1m 2 / g or more and 6m 2 / g or less. The BET specific surface area is 0.1m2 When the BET specific surface area is 10 m 2 When the surface area is 1.377 square meters or less, the surface area has the advantages that the oxidation of particles due to the influence of heat can be suppressed to a certain extent during film formation at high temperature, and the generation of rare earth oxides can be suppressed. The BET specific surface area is obtained by the BET single point method.
[0120] The film-forming material having a BET specific surface area within the above range can be obtained, for example, as follows: the film-forming material of the present invention is manufactured using the preferred manufacturing method described later, and the type of raw materials used in the first step, the pulverizing conditions in the second step, and the sintering conditions in the fourth step are adjusted.
[0121] The film-forming material of the present invention can be in powder form or granulated into a particle form. From the perspective of making the plasma corrosion resistance of the present invention excellent and making the fluidity of the film-forming material good and improving the supply of the film-forming material during film formation, it is preferably in a particle form. Regardless of the form, the average particle size of the primary particles of the film-forming material observed in a scanning electron microscope (SEM) is preferably 0.1 μm or more and 1.0 μm or less. When the average particle size of the primary particles is set within the above range, it has the following advantages: the kinetic energy of the particles becomes relatively the same, and it is easy to obtain a uniform film quality. In addition, when the average particle size of the primary particles is set to 1.0 μm or less, it has the following advantages: when the film-forming material of the present invention is in a particle form, since there are particles of appropriate size in the particles, the particle strength (the strength that can maintain the particle shape against external forces) is improved, and the supply of raw materials is improved. From these viewpoints, the average particle size of the primary particles of the film-forming material of the present invention is more preferably 0.2 μm or more and 0.9 μm or less, and more preferably 0.4 μm or more and 0.7 μm or less. In order to make the average particle size of the primary particles within this range, for example, an appropriate rare earth compound can be selected in the first step of a suitable production method for the film-forming material described later, and the degree of crushing can be adjusted in the second step and the sintering temperature in the third step can be adjusted.
[0122] It should be noted that the average particle size is the average value of Feret diameters. Feret diameter refers to the distance between two parallel lines sandwiching a particle image. In the present invention, vertical lines are used as the parallel lines (horizontal Feret diameter).
[0123] In the present invention, for the film-forming material in particle form, the average particle size of the particles (hereinafter also referred to as "particle diameter") is preferably 10 μm or more and 60 μm or less. By setting the average particle size of the particles to this range, the fluidity of the film-forming material of the present invention is improved, and a smooth film is easily obtained. From this viewpoint, the average particle size of the particles is more preferably 15 μm or more and 55 μm or less, and further preferably 25 μm or more and 45 μm or less. In order to make the average particle size of the particles within this range, for example, the atomizer speed in the granulation conditions based on the spray dryer can be adjusted in the suitable manufacturing method for the film-forming material described later, and the sintering conditions of the fourth step can also be adjusted.
[0124] It should be noted that the average particle size mentioned here refers to the volume cumulative particle size D50 at the cumulative volume 50% by volume obtained by using a laser diffraction / scattering particle size / particle size distribution measuring device. The determination method of D50 is described in the embodiments described later. The average particle size of the particles mentioned here is the case where the sample is not subjected to ultrasonic treatment and is measured.
[0125] In the above-mentioned film-forming material in the form of particles, the particles contain primary particles and voids. When the void ratio calculated by observing the internal cross section of the particles with SEM and dividing the area of the voids in the cross section by the area of the particles is 10% or more, it has the advantage that energy (heat, etc.) is easily and evenly transferred to the inside of the particles, so it is preferably 15% or more, more preferably 15% or more, and particularly preferably 20% or more.
[0126] In addition, when the porosity is 35% or less, there are advantages that the particle strength is improved and a dense film is easily obtained, so it is preferably 30% or less, and further preferably 25% or less.
[0127] In order to obtain particles having the above-mentioned porosity, for example, a suitable manufacturing method for the film-forming material of the present invention described later can be adopted, and the concentration of the film-forming material precursor slurry used in the third step can be adjusted. In addition, the viscosity of the slurry can be appropriately adjusted. The porosity is measured based on an image in which more than 30% of the cross-sectional area of a particle is included in one image. In addition, the image of the particle cross section uses an image in which at least 50 primary particles appear in one particle cross section. The specific method for measuring the porosity will be described in the examples described later.
[0128] In the present invention, the film-forming material in particle form preferably has an appropriate crushing pressure. More specifically, from the viewpoint that the particles are not easily damaged during transportation, the crushing pressure measured by a SEM indenter is preferably 25 kPa or more, and from this viewpoint, it is more preferably 50 kPa or more, and further preferably 75 kPa or more. From the viewpoint that the particles are not too hard and the adhesion with the substrate during film formation is easily improved, the crushing pressure of the film-forming material in particle form measured by a SEM indenter is preferably 130 kPa or less, more preferably 115 kPa or less, and further preferably 100 kPa or less. In addition to being measured by the method described in the embodiments described later, the crushing pressure measured by the SEM indenter can also be measured by other machine models as long as a machine model with equal or higher accuracy is used. In order to obtain particles with the above-mentioned crushing pressure, for example, a suitable manufacturing method for the film-forming material of the present invention described later can be adopted, and the sintering temperature of the fourth step can be appropriately adjusted.
[0129] When the film-forming material of the present invention is in the form of particles, its bulk density (also referred to as "static apparent density") is preferably 1.3 g / cm 3 From this point of view, the bulk density is more preferably 1.4 g / cm 3 More preferably, 2.0 g / cm 3 above.
[0130] In addition, from the viewpoint of raw material supply and handling properties, the bulk density is preferably 3.0 g / cm 3 From this point of view, the bulk density is more preferably 2.7 g / cm 3 Below, more preferably 2.4 g / cm 3 the following.
[0131] The bulk density can be measured by the method described in the examples described below, but other machine models may be used as long as the measurement accuracy is equal to or higher.
[0132] The film-forming material having a bulk density within the above range can be produced by, for example, using an appropriate production method described below to produce the film-forming material of the present invention, and adjusting the crushing conditions and the slurry concentration during spraying in a spray dryer.
[0133] 2. Method for manufacturing film-forming material
[0134] Next, a suitable method for manufacturing the film-forming material of the present invention is described. When the film-forming material of the present invention is a granule, it is suitable to be manufactured using a manufacturing method having the following steps 1 to 4. When the film-forming material is a powder that is not a granule, for example, it is considered that the granulation of the third step is not performed and the fourth step is provided.
[0135] · First step: a step of reacting a rare earth compound with hydrofluoric acid to obtain a film-forming material precursor.
[0136] · Second step: A step of crushing the film-forming material precursor obtained in the first step to obtain a film-forming material precursor slurry.
[0137] · Third step: a step of granulating the film-forming material precursor slurry obtained in the second step using a spray dryer to obtain a granulated product.
[0138] Step 4: A step of firing the granulated product obtained in step 3 at a temperature of 300° C. to 900° C. to obtain a granular film-forming material containing rare earth fluoride (REF3) and rare earth oxyfluoride (RE-OF).
[0139] The rare earth compound used in the first step includes a rare earth compound that is poorly soluble or insoluble in water.
[0140] Hereinafter, each step will be described in detail.
[0141] (1st step)
[0142] This step is a step of obtaining a film-forming material precursor.
[0143] First, after rare earth compound and pure water are mixed to form a solution or slurry of a specified concentration, hydrofluoric acid (HF aqueous solution) is added dropwise to the solution or slurry to perform fluorination reaction. Next, the slurry after the fluorination reaction is filtered to obtain a filter cake. At this time, from the viewpoint of working hours, filtration preferably uses a filter selected from a vacuum dehydrator, a centrifugal dehydrator and a filter press.
[0144] In the above-mentioned fluorination reaction, a partial fluorination reaction of the rare earth element is performed. This fluorination reaction is performed to obtain REF3 and RE-OF from the rare earth compound, and by partially stopping the fluorination reaction, a film-forming material containing RE-OF in addition to REF3 can be obtained.
[0145] Compared with other production methods such as sintering and oxidizing fluoride, the present production method is believed to facilitate obtaining a film-forming material having uniform crystallite sizes of REF3 and RE-OF by producing REF3 and RE-OF simultaneously.
[0146] From the viewpoint of appropriately controlling the degree of progress of the fluorination reaction, the ratio MF / MRE of the number of moles of rare earth elements (RE) from the rare earth compound to the number of moles of fluorine atoms (F) from hydrofluoric acid is preferably greater than 1.4 and less than 3.0, more preferably greater than 1.5 and less than 2.8, and further preferably greater than 1.6 and less than 2.5. The amount of hydrofluoric acid actually used can be appropriately adjusted within the above range according to the target ratio of REF3 and RE-OF in the film-forming material.
[0147] As the rare earth compound used in the first step, it is preferred to use a rare earth compound that is poorly soluble or insoluble in water. As the rare earth compound that is poorly soluble or insoluble in water, one or more selected from rare earth carbonates, rare earth oxalates and rare earth hydroxides can be cited. The reactivity of these compounds with hydrofluoric acid is moderately high. In this way, by making the reactivity of the rare earth compound with hydrofluoric acid moderately high and at least containing a rare earth compound that is poorly soluble or insoluble in water, the fluorination reaction is easily carried out at a moderate speed and uniformly when hydrofluoric acid is reacted with the rare earth compound.
[0148] It should be noted that, as the rare earth compound, a rare earth oxide can also be used, but its reactivity with hydrofluoric acid is lower than that of the above-mentioned compounds, so the fluorination reaction takes time.
[0149] Examples of the precursor obtained in the first step include components in which a part of the radical of a rare earth compound (for example, a carbonate radical in the case of a rare earth carbonate) is replaced with a fluorine atom.
[0150] In the present production method in which the suitable range of MF / MRE is more than 1.4 and less than 3.0 as described above, it is preferable to use a rare earth compound that is poorly soluble or insoluble in water. The reason for this is as follows.
[0151] If only a water-soluble rare earth compound is used as the rare earth compound, REF3 is generated when an aqueous solution of the water-soluble rare earth compound is reacted with hydrofluoric acid. S ) is set as MRE S When MF / MRE S If the ratio is less than 3.0, unreacted water-soluble rare earth compound may remain. When only water-soluble rare earth compound is used as rare earth compound and MF / MRE=MF / MRE SWhen it is more than 1.4 and less than 3.0, unreacted water-soluble rare earth compounds will remain, and only REF3 can be recovered by solid-liquid separation, and unreacted water-soluble compounds cannot be recovered in the form of solids by solid-liquid separation. If the whole amount is dried without solid-liquid separation, although the unreacted water-soluble rare earth compounds can be recovered in the form of solids, not only is the cost high, but REF3 and fluorine-free rare earth compounds are also mixed. During the firing in the fourth step described later, the crystallite size of the component that directly remains in the form of REF3 is likely to be much larger than the crystallite size of RE-OF generated by the reaction of REF3 and fluorine-free rare earth compounds.
[0152] In addition, when both water-soluble rare earth compounds and water-insoluble or insoluble rare earth compounds are used as rare earth compounds, the water-soluble rare earth compounds have high reactivity with hydrofluoric acid and tend to preferentially generate REF3. S When it is less than 3, REF3 is generated, except for MF / MRE S In the case of REF3, unreacted water-soluble compounds will remain. Since rare earth compounds that are poorly soluble or insoluble in water are hardly fluorinated, REF3 and fluorine-free parts will still exist mixedly.
[0153] In MF / MRE S When it is greater than 3, the rare earth compound that is poorly soluble or insoluble in water is uniformly partially fluorinated, but there is a difference in the fluorine concentration between the compound and REF3. As a whole, the fluorination is not uniformly carried out, and it is possible that REF3 with a relatively large crystallite size is generated due to the firing in the fourth step described later. In order to suppress this effect as much as possible, it is preferred to reduce the amount of REF3 present at the beginning of the firing in the fourth step described later as much as possible. In addition, since the REF3 generated by fluorination is extremely small particles, from the viewpoint of filterability in the filtration in the first step, it is also preferred to reduce the amount of REF3 generated by fluorination as much as possible. Therefore, the rare earth elements (REF3) from the rare earth compounds that are poorly soluble or insoluble in water are N ) molar number MRE N Rare earth elements (RE S ) molar number MRE S MRE N / MRE S It is preferably 1 or more, more preferably 2 or more, further preferably 5 or more, and particularly preferably 10 or more.
[0154] It should be noted that the most preferred is MRE S =0(MRE N / MRE S=∞), that is, instead of using water-soluble rare earth compounds, only using rare earth compounds that are poorly soluble or insoluble in water. If only using rare earth compounds that are poorly soluble or insoluble in water, the whole is fluorinated uniformly. If only using rare earth compounds that are poorly soluble or insoluble in water, a uniformly fluorinated precursor can be obtained, and during the firing in the fourth step described later, the precursor decomposes to generate REF3 and RE-OF, so the crystallite size of REF3 will not be excessively larger than the crystallite size of RE-OF, and it is easy to obtain a film-forming material within the range of the desired crystallite size ratio.
[0155] Furthermore, if only a rare earth compound that is poorly soluble or insoluble in water is used, very small particles of REF3 will not be generated during fluorination, so there is also an advantage that filtration is extremely easy.
[0156] The addition rate of the hydrofluoric acid may be, for example, 1 to 50 mol / min, but is not limited thereto.
[0157] (Second step)
[0158] In this process, the film-forming material precursor is crushed to obtain a film-forming material precursor slurry. In the crushing, either dry crushing or wet crushing can be applied, but wet crushing is preferred in terms of making the particle size distribution during crushing sharp and easily obtaining particles with uniform particle size. The crushing can be implemented in one stage, or it can be implemented in two or more stages. From the perspective of cost and labor and time, it is preferred to crush in one stage. In the case of dry crushing, various dry crushers such as a pestle, jet mill, ball mill, hammer mill and pin mill can be used. On the other hand, in the case of wet crushing, various wet crushers such as a ball mill and bead mill can be used.
[0159] The degree of crushing in the second step is preferably such that the volume cumulative particle diameter D50 when the cumulative volume is 50% by volume measured by a laser diffraction / scattering particle diameter / particle size distribution measuring device is 0.1 μm or more and 2.0 μm or less. By crushing in such a way that the D50 is in the above range, it is easy to make uniform particles when the spray dryer is operated in the third step described later. If the particles are uniform, it is not easy to generate pores in the film during film formation, and the corrosion resistance of the film to plasma etching is improved. From this point of view, it is more preferable to crush in such a way that the D50 is 0.5 μm or more and 1.5 μm or less.
[0160] The concentration of the film-forming material precursor slurry supplied to the third step after the crushing in the second step is preferably 50 g / L or more and 1500 g / L or less, and more preferably 100 g / L or more and 1000 g / L or less. By setting the concentration of the slurry within this range, it has the advantage of being easy to obtain the above-mentioned porosity. In addition, it is possible to suppress excessive energy consumption in subsequent steps, and to make the viscosity of the slurry moderate, so that the spraying in the third step can be stabilized.
[0161] (Step 3)
[0162] In the third step, the slurry obtained in the second step is granulated using a spray dryer to obtain granulated material of the film-forming material precursor. The rotation speed of the atomizer when the spray dryer is operated is preferably 5000 min -1 Above and 30000min -1 By making the rotation speed 5000min -1 On the other hand, by setting the rotation speed to 30000min -1 From these viewpoints, the rotation speed of the atomizer is more preferably 6000 min -1 Above and 25000min -1 the following.
[0163] The inlet temperature when the spray dryer is operated is preferably 150° C. to 300° C. By setting the inlet temperature to 150° C. or higher, the solid content can be fully dried, and particles with less residual water content can be easily obtained. On the other hand, by setting the inlet temperature to 300° C. or lower, wasteful energy consumption can be suppressed.
[0164] (Step 4)
[0165] In this process, the granulated material obtained in the fourth process is calcined to obtain a film-forming material in the form of particles of rare earth fluoride oxide containing rare earth fluoride. The degree of this calcination is a factor that controls the crystallite size. In detail, the calcination temperature is preferably 300°C to 900°C. By setting the calcination temperature to above 300°C, there is an advantage of being able to remove impurities such as carbon from the raw material. On the other hand, by setting the calcination temperature to below 900°C, there are advantages such as being easy to make the crystallite size of REF3 below the prescribed value, easy to obtain the prescribed ratio of the present invention, and easy to obtain the target composition. From these viewpoints, the calcination temperature is more preferably 400°C to 800°C, and further preferably 500°C to 700°C.
[0166] The present inventors believe that since the present method is carried out at a relatively low temperature and the number of firing steps from the reaction of the fluoride and the rare earth compound to the production of the film-forming material is only one, it is easy to control the crystallite size.
[0167] The calcination time is preferably 1 to 48 hours, provided that the calcination temperature is within the above range. It is more preferably 3 to 24 hours. The calcination atmosphere is not particularly limited, but from the perspective of cost, it is preferably carried out in an oxygen-containing atmosphere such as air.
[0168] The above-mentioned suitable manufacturing method is superior to the method of manufacturing the film-forming material by mixing REF3 and RE-OF which are separated in advance in terms of obtaining a film-forming material in which REF3 and RE-OF are uniformly mixed. By uniformly mixing REF3 and RE-OF, a uniform film is obtained during film formation, and such a film has excellent corrosion resistance to plasma etching.
[0169] When the film-forming material of the present invention is produced by the above-mentioned suitable production method, a mixture of REF3 and RE-OF can be obtained by decomposing the precursor by firing in the fourth step. However, it is considered that when at least RE is Y, Er or Yb, only RE5O4F7 with less oxygen is easily produced as RE-OF, and it is difficult to produce RE6O5F8, RE7O6F9 and REOF (RE1O1F1) containing more oxygen than RE5O4F7. It is also considered that when RE is at least one selected from Sm, Eu and Gd, Sm4O3F6, Eu4O3F6 and Gd4O3F6 with less oxygen content are easily produced as RE-OF.
[0170] 3. Film forming method
[0171] Next, a film forming method that can be used when forming a film using the film forming material of the present invention will be described.
[0172] Main film-forming methods applicable to the present invention include a sputtering method, a physical vapor deposition method (PVD method), and the like.
[0173] (1) Spraying method
[0174] As a method for thermally spraying the film-forming material of the present invention, flame spraying, high-velocity flame spraying, detonation spraying, laser spraying, plasma spraying, laser / plasma composite spraying, etc. can be applied.
[0175] (2) PVD method (Physical Vapor Deposition method)
[0176] PVD methods generally include sputtering, vacuum evaporation, and ion plating (see "Patent Map Classified by Technical Field: Chemical 16 Physical Evaporation" published on the homepage of the Japan Patent Office). Figure 4 .1.1-3”, etc.).
[0177] The film-forming material of the present invention can be applied to vacuum evaporation, sputtering and ion plating. Vacuum evaporation is a method of evaporating or sublimating a film-forming material in a vacuum, so that its vapor reaches a substrate as a film-forming object and accumulates to form a film. As vacuum evaporation, electron beam method and laser evaporation have sufficient energy for vaporizing powder containing rare earth fluoride oxides, so they are preferred. Sputtering is a method of forming a film in the following manner: using plasma or the like to make particles with high energy collide with a material (target), and the impact is used to knock out the material components, thereby causing the particles of the generated material components to accumulate on the substrate to form a film. In addition, ion plating is a film-forming method based on roughly the same principle as the evaporation method, and the difference lies in the following method: by passing the evaporated particles through the plasma, so that they are positively charged, a negative charge is applied to the substrate to attract the evaporated particles and accumulate them to form a film.
[0178] The film-forming material of the present invention can be suitably used in the above-mentioned various film-forming methods, and the film formed in this way has excellent corrosion resistance to plasma etching. As the substrate to be film-formed, various metals such as aluminum, various alloys such as aluminum alloys, various ceramics such as alumina, quartz, etc. can be used.
[0179] The porosity of the film obtained from the film-forming material of the present invention is preferably 10% or less, more preferably 5% or less. The lower limit of the porosity is 0%. In addition, the surface roughness Ra of the film obtained from the film-forming material is preferably 0.01 μm or more and 10 μm or less, more preferably 0.1 μm or more and 5 μm or less. The surface roughness Rz is preferably 0.1 μm or more and 100 μm or less, more preferably 1 μm or more and 50 μm or less. The porosity, surface roughness Ra and Rz can be measured by the method described in the embodiments described later.
[0180] In the X-ray diffraction measurement of the film using Cu-Kα rays, the ratio (S1' / S2') of the intensity of the main peak of RE-OF observed in the range of 2θ=20° to 60° to the intensity of the main peak of REF3 observed in the same range is obtained. For example, when S1' / S2' is 0.05 or more and 100 or less, it is preferred from the perspective of corrosion resistance. From this viewpoint, S1' / S2' is more preferably 0.1 or more and 10 or less, and further preferably 1 or more and 5 or less.
[0181] In addition, for the film obtained from the film-forming material of the present invention, in the X-ray diffraction measurement using Cu-Kα rays, the ratio (S0' / S1') of the intensity of the main peak of the rare earth oxide observed in the range of 2θ=20°~60° to the intensity of the main peak of the rare earth fluoride oxide observed in the same range is preferably less than 0.1, and more preferably less than 0.01.
[0182] The film of this embodiment can be used for coating the inside of semiconductor manufacturing equipment or its components, such as the vacuum chamber in the etching device and the sample stage or chuck, focus ring, etching gas supply port in the chamber, by utilizing its excellent plasma corrosion resistance. In addition, the film of this embodiment can also be used for various plasma processing devices and components of chemical plant equipment other than the inside of semiconductor manufacturing equipment or its components. As described in the examples described later, the film of this embodiment shows excellent corrosion resistance to both fluorine-based plasma and chlorine-based plasma.
[0183] Example
[0184] Hereinafter, the present invention will be described in more detail using examples, but the scope of the present invention is not limited to these examples.
[0185] [Example 1]
[0186] (1st step)
[0187] After 20 mol of yttrium (Y) converted into yttrium carbonate hydrate (Y2(CO3)3·nH2O) and pure water are put into a synthesis tank, they are fully stirred and mixed to prepare a slurry containing yttrium at a concentration of 0.5 mol / L. A 50 mass% HF aqueous solution is added to the slurry at 2.1 mol / min to achieve a ratio of fluorine atoms (F) in the added HF aqueous solution to yttrium atoms (Y) in the slurry F / Y (molar ratio) = 2.1, and a partial fluorination reaction is carried out. Next, the slurry after the fluorination reaction is filtered to obtain a filter cake of a film-forming material precursor.
[0188] (Second step)
[0189] Pure water was added to the film-forming material precursor filter cake obtained in the first step, and the film-forming material precursor was crushed with a bead mill so that the D50 measured by a laser diffraction / scattering particle size distribution analyzer was 0.8 μm. After crushing, pure water was further added to prepare a 500 g / L film-forming material precursor slurry.
[0190] It should be noted that regarding D50, in the particle diameter measurement method described later, after adding the sample to the chamber of the sample circulator of MICROTRAC3300EXII until the device determines that it is an appropriate concentration, an ultrasonic dispersion treatment is performed at 40 W for 5 minutes using an ultrasonic irradiation device equipped with the device before measurement. Other than this, the measurement is performed using the same measurement method as the particle diameter.
[0191] (Step 3)
[0192] The film-forming material precursor slurry obtained in the second step was granulated and dried using a spray dryer (manufactured by Ohkawara Processing Machinery Co., Ltd.) using a rotating disk as an atomizer to obtain granules. The operating conditions of the spray dryer are as follows.
[0193] Slurry supply speed: 75mL / min
[0194] Atomizer speed: 18000min -1
[0195] Inlet temperature: 250℃
[0196] (Step 4)
[0197] The granulated material obtained in the third step is fired in an electric furnace under an air atmosphere to obtain granulated particles. The firing temperature is set to 600° C. and the firing time is set to 5 hours. The shape of the particles is approximately spherical. In this way, a film-forming material in the form of particles containing yttrium fluoride and yttrium oxyfluoride is obtained.
[0198] [Example 2]
[0199] In the first step of Example 1, the addition amount of the 50 mass % HF aqueous solution was set to an amount such that the ratio of F in HF to Y in the slurry (F / Y (molar ratio)) = 2.5. Except for this, the same operation as in Example 1 was carried out to obtain a film-forming material in the form of particles containing yttrium fluoride and yttrium fluoride oxide.
[0200] [Example 3]
[0201] In the first step of Example 1, the amount of 50 mass % HF aqueous solution added was set to an amount that makes the ratio of F in HF to Y in the slurry F / Y (molar ratio) = 2.8. Except for this, the same operation as Example 1 was carried out to obtain a film-forming material in the form of particles containing yttrium fluoride and yttrium fluoride oxide.
[0202] [Example 4]
[0203] In the first step of Example 1, the addition amount of the 50 mass % HF aqueous solution was set to an amount that makes the ratio of F in HF to Y in the slurry F / Y (molar ratio) = 1.6. Except for this, the same operation as Example 1 was carried out to obtain a film-forming material in the form of particles containing yttrium fluoride and yttrium fluoride oxide.
[0204] [Example 5]
[0205] The atomizer speed in the third step of Example 2 was changed to 12000 min -1 , except for this, the same operation as in Example 2 was carried out to obtain a film-forming material in the form of particles containing yttrium fluoride and yttrium oxyfluoride.
[0206] [Example 6]
[0207] In the second step of Example 2, the film-forming material precursor is crushed so that D50 is 0.3 μm, and pure water is further added after crushing to prepare a 350 g / L slurry. In the third step, the mixed slurry is sprayed with a two-fluid nozzle instead of a rotating disk. Except for this, the same operation as Example 2 is performed to obtain a film-forming material in the form of particles containing yttrium fluoride and yttrium fluoride oxide.
[0208] [Example 7]
[0209] In the first step of Example 1, instead of using yttrium carbonate hydrate, gadolinium carbonate hydrate (Gd2(CO3)3·nH2O) converted to 10 mol of gadolinium (Gd) and pure water are put into a synthesis tank, and then stirred and mixed sufficiently to prepare a slurry containing gadolinium at a concentration of 0.2 mol / L. A 50% by mass HF aqueous solution is added dropwise to the slurry to achieve an amount in which the ratio of fluorine atoms (F) in the added HF aqueous solution to gadolinium atoms (Gd) in the slurry is F / Gd (molar ratio) = 2.8. Except for the above points, the same operation as in Example 1 is performed to obtain a film-forming material in the form of particles containing gadolinium fluoride and gadolinium oxyfluoride.
[0210] [Example 8]
[0211] In the first step of Example 7, except that the amount of 50 mass % HF aqueous solution added was set to an amount such that the ratio of F in HF to Gd in the slurry (F / Gd (molar ratio)) = 2.5, the same operation as in Example 7 was carried out to obtain a film-forming material in the form of particles containing gadolinium fluoride and gadolinium oxyfluoride.
[0212] [Example 9]
[0213] In the first step of Example 7, except that the amount of 50 mass % HF aqueous solution added was set to an amount such that the ratio of F in HF to Gd in the slurry (F / Gd (molar ratio)) = 2.0, the same operation as in Example 7 was carried out to obtain a film-forming material in the form of particles containing gadolinium fluoride and gadolinium oxyfluoride.
[0214] [Example 10]
[0215] In the first step of Example 7, except that the amount of 50 mass % HF aqueous solution added was set to an amount such that the ratio of F in HF to Gd in the slurry (F / Gd (molar ratio)) = 1.8, the same operation as in Example 7 was carried out to obtain a film-forming material in the form of particles containing gadolinium fluoride and gadolinium oxyfluoride.
[0216] [Example 11]
[0217] In the first step of Example 1, instead of using yttrium carbonate hydrate, erbium carbonate hydrate (Er2(CO3)3·nH2O) converted to 10 mol of erbium (Er) and pure water are put into a synthesis tank, and then stirred and mixed to prepare a slurry containing erbium at a concentration of 0.2 mol / L. A 50 mass % HF aqueous solution is added dropwise to the slurry to reach an amount in which the ratio of fluorine atoms (F) to erbium atoms (Er) F / Er (molar ratio) = 2.7. Except for the above points, the same operation as in Example 1 is carried out to obtain a film-forming material in the form of particles containing erbium fluoride and erbium oxyfluoride.
[0218] [Example 12]
[0219] In the first step of Example 11, the amount of 50 mass% HF aqueous solution added was set to an amount that makes the ratio of F in HF to Er in the slurry F / Er (molar ratio) = 2.5. Except for this, the same operation as Example 11 was carried out to obtain a film-forming material in the form of particles containing erbium fluoride and erbium oxyfluoride.
[0220] [Example 13]
[0221] In the first step of Example 11, the amount of 50 mass % HF aqueous solution added was set to an amount that makes the ratio of F in HF to Er in the slurry F / Er (molar ratio) = 2.0. Except for this, the same operation as Example 11 was carried out to obtain a film-forming material in the form of particles containing erbium fluoride and erbium oxyfluoride.
[0222] [Example 14]
[0223] In the first step of Example 1, instead of using yttrium carbonate hydrate, ytterbium carbonate hydrate (Yb2(CO3)3·nH2O) converted to 10 mol of ytterbium (Yb) and pure water are put into a synthesis tank, and then stirred and mixed to prepare a slurry containing ytterbium at a concentration of 0.2 mol / L. A 50% by mass HF aqueous solution is added dropwise to the slurry to reach an amount in which the ratio of fluorine atoms (F) to ytterbium atoms (Yb) F / Yb (molar ratio) = 2.7. Except for the above points, the same operation as in Example 1 is performed to obtain a film-forming material in the form of particles containing ytterbium fluoride and ytterbium oxyfluoride.
[0224] [Example 15]
[0225] In the first step of Example 14, except that a 50 mass % HF aqueous solution was added dropwise in an amount of F / Yb (molar ratio) = 2.5 times, the same operation as in Example 14 was carried out to obtain a granular film-forming material containing ytterbium fluoride and ytterbium oxyfluoride.
[0226] [Example 16]
[0227] In the first step of Example 14, except that a 50 mass % HF aqueous solution was added dropwise in an amount of F / Yb (molar ratio) = 2.0 times, the same operation as in Example 14 was carried out to obtain a granular film-forming material containing ytterbium fluoride and ytterbium oxyfluoride.
[0228] [Comparative Example 1]
[0229] In the first step of Example 5, except that a 50 mass % HF aqueous solution was added dropwise to achieve F / Y (molar ratio) = 1.4, the same operation as in Example 5 was carried out to obtain a film-forming material in the form of particles containing yttrium oxyfluoride.
[0230] [Comparative Example 2]
[0231] In the first step of Example 5, except that a 50 mass % HF aqueous solution was added dropwise to achieve F / Y (molar ratio) = 1.0, the same operation as in Example 5 was carried out to obtain a film-forming material in the form of particles containing yttrium oxyfluoride.
[0232] [Comparative Example 3]
[0233] Yttrium fluoride (YF3) was calcined in an electric furnace under an atmospheric atmosphere at a calcination temperature of 1050°C for 12 hours. The calcined product was crushed by wet crushing so that D50 was 1 to 2 μm. After that, pure water was added to make a 500 g / L slurry, which was granulated by a spray dryer (atomizer: rotating disk). The operating conditions of the spray dryer are shown below.
[0234] Slurry supply speed: 300mL / min
[0235] Atomizer speed: 12000min -1
[0236] Inlet temperature: 200℃
[0237] The obtained granulated powder was calcined in an electric furnace under air atmosphere at a calcination temperature of 600° C. for 12 hours to obtain a film-forming material in the form of particles containing yttrium fluoride and yttrium oxyfluoride.
[0238] [Comparative Example 4]
[0239] 30 wt% of yttrium oxide (Y2O3) and 70 wt% of yttrium ammonium fluoride complex salt ((YF3)3NH4F·H2O) were mixed. Then, pure water was added to make a 500 g / L slurry, which was granulated using a spray dryer (atomizer: rotating disk). The operating conditions of the spray dryer are as follows.
[0240] Slurry supply speed: 300mL / min
[0241] Atomizer speed: 12000min -1
[0242] Inlet temperature: 200℃
[0243] The obtained granulated powder was calcined in an electric furnace under a vacuum atmosphere at a calcination temperature of 900° C. for 12 hours to obtain a film-forming material in the form of particles containing yttrium fluoride and yttrium oxyfluoride.
[0244] [Comparative Example 5]
[0245] Yttrium fluoride (YF3, D50 = 0.6 μm) and Y5O4F7 (D50 = 1 μm) were mixed to form a slurry, which was granulated using a spray dryer (atomizer: rotating disk) to obtain a film-forming material in the form of particles containing yttrium fluoride and yttrium oxyfluoride. The operating conditions of the spray dryer are as follows.
[0246] Slurry supply speed: 300mL / min
[0247] Atomizer speed: 9000min -1
[0248] Inlet temperature: 200℃
[0249] [Comparative Example 6]
[0250] In the first step of Example 7, except that a 50 mass % HF aqueous solution was added dropwise so as to make F / Gd (molar ratio) = 1.0, the same operation as in Example 7 was carried out to obtain a particle-shaped film-forming material containing gadolinium fluoride and gadolinium oxyfluoride.
[0251] <Evaluation of film-forming materials>
[0252] The following evaluations were performed on the film-forming materials and the thermally sprayed films of the respective Examples and Comparative Examples. Various measured values obtained by these evaluations are shown in Tables 1 and 2.
[0253] (Determination of oxygen content)
[0254] The oxygen content (mass %) of the film-forming material was measured by a melting-infrared absorption method in an inert gas (using a halogen trap).
[0255] (X-ray diffraction measurement)
[0256] X-ray diffraction measurement was carried out under the following conditions to determine the intensities (S0 to S2) of the main peaks of REF3, RE-OF and RE2O3. The X-ray diffraction peak intensities in Table 1 are peak intensity ratios relative to the main peaks from the crystalline phase of each compound, which represent the values when the peak intensity of the main peak at 2θ=20° to 60° is set to 100. The peak intensity ratio mentioned here is a peak height ratio. However, when determining the peak intensity ratio, except for RE2O3, the combination of Yb5O4F7 and YbF3, the combination of Y1O1F1 and YF3, and the combination of Gd1O1F1 and GdF3, the peak heights of the main peaks from the crystalline phase of each compound are not used directly, but the peak heights of the above peaks are converted into the peak heights of the main peaks for use.
[0257] The crystallite size is calculated based on X-ray diffraction measurement of the film-forming material under the following conditions and in accordance with "12. Measurement of crystallite size and inhomogeneous strain" of JIS K0131-1996 "General Rules for X-ray Diffraction Analysis". At this time, the X-ray diffraction data based on CuKα rays measured under the following conditions are separated into diffraction data based on Cu-Kα1 rays and Cu-Kα2 rays, and the diffraction pattern of only Cu-Kα1 rays is drawn to obtain the half-peak width and diffraction angle. In addition, Si as a standard substance is measured and the half-peak width is corrected.
[0258] Specifically, in the film-forming materials obtained in Examples 1 to 6, RE-OF is a Y5O4F7 phase. The crystallite size of YF3 is calculated from the half-peak width of the (020) peak, and the crystallite size of Y5O4F7 is calculated from the half-peak width of the (010 0) peak of Y5O4F7, using the sheller formula (D = Kλ / (βcosθ)).
[0259] In the film-forming materials obtained in Examples 7 to 10, RE-OF was a Gd4O3F6 phase. The half-widths of GdF3 and Gd4O3F6 were calculated from the above-mentioned specific peaks using the Sheller formula (D = Kλ / (βcosθ)).
[0260] In the film-forming materials obtained in Examples 11 to 13, RE-OF was an Er5O4F7 phase. ErF3 and Er5O4F7 were calculated from the half-width of the above-mentioned specific peaks using the Sheller formula (D = Kλ / (βcosθ)).
[0261] In Examples 14 to 16, RE-OF is a Yb5O4F7 phase. YbF3 and Yb5O4F7 were calculated from the half-width of the above-mentioned specific peaks using the Sheller formula (D = Kλ / (βcosθ)).
[0262] In addition, as the value of K, 0.94 described in "12. Measurement of crystallite size and inhomogeneous strain" of JIS K 0131-1996 "General rules for X-ray diffraction analysis" was used.
[0263] The calculation of the crystallite size was performed on X-ray diffraction data measured under the following conditions using comprehensive powder X-ray analysis software PDXL2 Version 2.9.1.0 (manufactured by Rigaku Corporation).
[0264] For Comparative Examples 1 to 6, the half-width of a specific peak of a properly generated phase was obtained. In Comparative Examples 1, 3 to 5, RE-OF was a Y5O4F7 phase; in Comparative Example 2, RE-OF was a Y1O1F1 phase; and in Comparative Example 6, RE-OF was a Gd1O1F1 phase.
[0265] Using the crystallite sizes obtained in this way, the crystallite size ratio was calculated by the following calculation formula.
[0266] (Ratio of crystallite size) = (crystallite size of REF3) / (crystallite size of RE-OF)
[0267] The XRD pattern obtained in Example 1 is expressed as Figure 1 .
[0268] <X-ray diffraction measurement conditions>
[0269] ·Device: Ultima IV (made by Rigaku Co., Ltd.)
[0270] ·Ray source: Cu-Kα ray
[0271] Tube voltage: 40kV
[0272] Tube current: 40mA
[0273] Scanning speed: 2 degrees / min
[0274] Stepping: 0.02 degrees
[0275] Scanning range: 2θ=20°~60°
[0276] (Measurement of average particle size of primary particles)
[0277] In the field of view of the SEM (20000 times) where a part of the particle cross section is observed, the Feret diameter of each primary particle is measured, and 100 particles with a Feret diameter of more than 0.1 μm are measured and averaged, and the obtained value is used as the average particle size of each primary particle. The reason for excluding the length equivalent to less than 0.1 μm is that the boundary line of the particle is not clear and the measurement error of the particle size is also large. As SEM, JSM-7900F made by JEOL Co., Ltd. is used. The accelerating voltage is set to 4 kV.
[0278] In addition, the method for preparing a sample showing a particle cross section is as follows.
[0279] After the particles were embedded in epoxy resin, ion milling was performed to produce a sample in which the cross section of the particles was exposed.
[0280] (Determination of void ratio)
[0281] For the SEM image of the field of view of the above-mentioned SEM (20,000 times, accelerating voltage of 4 kV), use the image processing software ImageJ, and use the menu bar Adjust→Color Thereshold (threshold Brightness 75)→AnalyzeParticle (particle analysis) to calculate the particle area ratio (% Area, % Area), and use the remaining area ratio as the porosity. The porosity is the average value obtained by measuring 5 particle cross sections. As the SEM image, an image of particles that meet the above conditions is used. It should be noted that one of the images used in the porosity measurement of Example 1 is shown in Figure 2 middle.
[0282] (Determination of crushing pressure)
[0283] The crushing pressure was measured using a SEM indenter under the following measurement conditions.
[0284] The sample for the SEM indenter is prepared by dispersing it on a quartz block using isopropyl alcohol (IPA) as a dispersion medium. The sample thus prepared is placed together with the quartz block on the sample mounting portion of the following device, and a stress-strain curve is obtained in the form of an in situ compression test of every three particles in each particle. The peak value (maximum value) of the stress is read as the value of the crushing stress, and the crushing pressure is calculated by dividing it by the area of the front end of the indenter. The crushing pressure is the average value of three values. The SEM image of the crushing pressure measurement of Example 1 is represented as Figure 3 and Figure 4 .
[0285] <Crushing pressure measurement conditions>
[0286] · Equipment: FT-NMT04 (manufactured by Femto Tools)
[0287] · Equipped SEM: SUPRA 55VP (Carl Zeiss, observation magnification 2000 times)
[0288] Sensor used: FT-S20000-(registered appearance)-FP-10um
[0289] (Diamond indenter, flat punch (indenter tip φ10μm))
[0290] ·Measurement mode: Compression
[0291] ·Insert load: Maximum 20000μN, Insert displacement: Maximum 10μm
[0292] (Determination of BET specific surface area)
[0293] The BET specific surface area was determined by the BET 1-point method using Macsorb manufactured by Mountech as a measuring device. A mixed gas of 30% by volume nitrogen and 70% by volume helium was used as a measuring gas, and pure nitrogen was used as a calibration gas. The slurry used in the measurement of the BET specific surface area was dried by drying 20 g of the slurry in an environment of 120° C. for 2 hours.
[0294] (Determination of particle diameter)
[0295] The particle diameter was measured using MICROTRAC 3300EXII manufactured by MicrotracBEL Co., Ltd. During the measurement, a 0.2 mass % sodium hexametaphosphate aqueous solution was used as a dispersion medium, and a sample (particles) was added to the chamber of the sample circulator of MICROTRAC 3300EXII until the device determined that the concentration was appropriate.
[0296] (Determination of Bulk Density)
[0297] Bulk density (g / cm 3 ) was determined using a bulk specific gravity measuring instrument manufactured by Tokyo Kurachi Scientific Instruments Mfg. Co., Ltd. in accordance with JIS K 5101-12-1.
[0298]
[0299] As shown in Table 1, in the film-forming materials of each example, rare earth fluoride (REF3) and rare earth fluoride oxide (RE-OF) were observed in the X-ray diffraction measurement, and the crystallite size ratio S REF3 / S RE-O-FOn the other hand, in Comparative Examples 1, 2, and 6, no rare earth fluoride (REF3) was observed, and in Comparative Examples 3 to 5, the ratio S of the crystallite size was REF3 / S RE-O-F Outside the range of 0.90 or more and 1.35 or less.
[0300] (Manufacturing of sprayed films)
[0301] The film-forming materials of the respective examples and comparative examples were formed into films by the following method to form thermal sprayed films.
[0302] An aluminum alloy plate was used as a substrate. The surface of the substrate was plasma sprayed. A TWIN-SYSTEM 10-V manufactured by Plasma-Technik was used as a supply device for film-forming materials. A F4 manufactured by Sulzer-Metco was used as a plasma spraying device.
[0303] Plasma spraying was performed under the conditions of a stirring speed of 50%, a carrier gas flow rate of 2.5 L / min, a supply scale of 10%, a plasma gas of Ar / H2, a power of 35 kW, and a device-substrate distance of 150 mm to obtain a film thickness of about 150 μm.
[0304] (Analysis of membrane composition)
[0305] The films of the examples and comparative examples obtained by the above method were subjected to XRD measurement in the same manner as for the film-forming material, and the intensity ratio of the main peak was determined.
[0306] (Measurement of Surface Roughness of Film)
[0307] The surface roughness of the thermal sprayed film on the 20 mm square aluminum alloy plate on which the thermal sprayed film was formed by the above method was measured.
[0308] The arithmetic mean roughness (Ra) and the maximum height roughness (Rz) (JIS B 0601: 2001) were determined using a stylus surface roughness tester (JIS B0651: 2001). As a stylus surface roughness tester, SJ-210 manufactured by Mitutoyo was used. The measurement conditions were evaluation length: 5 mm, measurement speed: 100 μm / s. The average value of the three points was determined.
[0309] (Porosity of membrane)
[0310] The 20 mm × 5 mm surface of the film in the 20 mm square (5 mm thick) aluminum alloy plate formed by the sprayed film using the above method was mirror-polished, and the cross-section of the film observed by SEM (1000 times, accelerating voltage of 10 kV) was image processed using the same method as the above-mentioned porosity measurement to calculate the porosity.
[0311] (Determination of etching rate)
[0312] Kapton tape was attached to half of the film of a 20 mm square aluminum alloy plate (5 mm thick) formed by the above method, and the plate was placed in the chamber of an etching device (RIE-10NR manufactured by SAMCO) with the film facing upward, and plasma etching was performed. The plasma etching conditions are as follows.
[0313] The etching rate was measured by measuring the step difference between the plasma exposed surface and the non-exposed surface after the tape was peeled off after plasma irradiation using the surface roughness measurement described above. Three measurement points were set for each film, and the average value of the three points was calculated.
[0314] <Plasma Etching Conditions>
[0315] Atmosphere gas: CF4 / O2 / Ar=40 / 20 / 40 (cc / min)
[0316] High frequency power: RF 300W
[0317] Pressure: 5Pa
[0318] Etching time: 5 hours
[0319]
[0320] (Inclusion of heterogeneous phases means that there are altered products caused by thermal spraying in REF3.)
[0321] In Table 2, the surface roughness of the thermal sprayed films of each embodiment is generally smaller than that of each comparative example. In addition, the porosity of the thermal sprayed films of each embodiment is smaller and the etching rate is lower than that of each comparative example. It can be seen that the films formed by forming the film-forming materials of each embodiment are denser and have excellent corrosion resistance to plasma etching than the films obtained in each comparative example.
[0322] Industrial Applicability
[0323] According to the present invention, a film-forming material capable of producing a dense film having excellent corrosion resistance to plasma etching can be provided.
Claims
1. A film-forming material, wherein: Rare earth fluoride (REF3) and rare earth oxyfluoride (RE-OF) were observed in X-ray diffraction measurement, and the crystallite size of REF3 (S REF3 ) relative to the crystallite size of RE-OF (S RE-O-F ) ratio (S REF3 / S RE-O-F ) is greater than or equal to 0.90 and less than or equal to 1.
35.
2. The film-forming material according to claim 1, wherein The crystallite size of each of REF3 and RE-OF is 40 nm or more and 100 nm or less.
3. The film-forming material according to claim 1 or 2, wherein The average particle size of the primary particles observed under a scanning electron microscope (SEM) is 0.1 μm or more and 1.0 μm or less. The film-forming material according to claim 1 or 2, which is in the form of particles.
5. The film-forming material according to claim 4, wherein The void ratio in the internal cross section of the particle observed by SEM is 10% or more and 35% or less. The film-forming material according to claim 4 , wherein the crushing pressure measured by a SEM indenter is 25 kPa or more and 130 kPa or less.
7. The film-forming material according to claim 4, wherein The average particle size of the particles is 10 μm or more and 60 μm or less.
8. The film-forming material according to claim 1 or 2, which has a bulk density of 1.3 g / cm 3 The above particles. 9 . The film-forming material according to claim 1 , wherein the oxygen content is 1% by mass or more and 9% by mass or less.
10. The film-forming material according to claim 1 or 2, wherein The rare earth element (RE) is at least one selected from yttrium (Y), gadolinium (Gd), erbium (Er) and ytterbium (Yb). 11 . A method for producing a film, comprising forming a film of the film-forming material according to claim 1 or 2 by a sputtering method or a PVD method.
Citation Information
Patent Citations
Thermal spray material and process for preparing same
US20150096462A1
Thermal spray material, thermal spray coating and thermal spray coated article
US20160326623A1
Yttrium fluoride spray material, yttrium oxyfluoride-deposited article, and making methods
US20170114440A1
